STRATEGIC MACROECONOMIC DETERMINANTS OF BANKING PROFITABILITY: A TWO-COUNTRY ASEAN STUDY - Rahma Febrianti; Wirda Mardyaningsih (Surplus: Jurnal Riset Mahasiswa Ekonomi, Manajemen, dan Akuntansi, 2025)
This study examines the influence of Foreign Direct Investment (FDI) and Gross Domestic Product (GDP) on the Return on Assets (ROA) of publicly listed banks in Indonesia and Malaysia using a panel data approach with Bank Focus as the data source. The analysis aims to provide a deeper understanding of how macroeconomic indicators shape banking profitability in two countries with differing economic structures. The findings indicate that in Malaysia, FDI has no significant effect on ROA, while GDP exerts a positive and significant influence on banking profitability. In contrast, for Indonesian banks, FDI demonstrates a significant negative effect on ROA, whereas GDP shows no significant impact. These results highlight that the sensitivity of banking profitability to macroeconomic conditions varies across countries, suggesting that financial strategies and banking policies must be adapted to the specific economic context of each nation.